Development of pose estimation machine learning media to introduce two-dimensional shapes - Manik, Stevani Rebekka Saulina; Safarini TLS, Desyarti; Harditya, Arya (International Journal of Mathematics and Sciences Education, 2023)
Most of the students needed help comprehending the geometry material concepts provided by the teacher. Learning media is one aspect that influences students' comprehension of geometry concepts. With the current situation, the use of the learning media such as pictures in a book or color-shaped paper does not relevant anymore. This project aims for a valid two-dimensional learning media, Pose Estimation Machine Learning (PEML), following students' characteristics and cognitive development. The developed online media facilitates visuals and allows students to move and perform motoric activities to represent the shapes. The method of the research was by using adjusted R&D steps: 1) preliminary investigation, 2) design, 3) realization, 4) test, evaluation, and revision, and 5) implementation. The participants of this study are second-grade students in a private elementary school in Central Jakarta. Data from the observation, students' worksheets, and interviews show that students were enthusiastic during the learning while they could still achieve the learning outcomes. The result indicates that PEML can be a medium for introducing two-dimensional topics.